ANALISIS PENGARUH PERDAGANGAN INTRA DAN EKSTRA REGIONAL TERHADAP PERTUMBUHAN EKONOMI NEGARA ANGGOTA ASEAN - Desmayani Siregar (Universitas Negeri Medan, 2018)
The aim of this research is to examine the effect of intra- regional trade in ASEAN, extra regional ASEAN, foreign direct investment, inflation and population to the economic growth of ASEAN member countries. The method of analysis which is used in the research is regression panel with Eviews software 7. The population which is used in this research is ten ASEAN member countries with study period from year 2010 till year 2014. The result showed that, intra- regional trade in ASEAN, extra regional ASEAN, foreign direct investment, inflation and total population simultaneously has a significant effect on the economic growth of ASEAN member countries. Partially, intra-regional ASEAN trade and the number of population have negative effect on the economic growth of ASEAN member countries. While intra- regional trade, foreign direct investment and inflation partially have positive effect on the economic growth on ASEAN member countries.